Bioactive compounds and physicochemical properties of dairy products supplemented with plantain and turmeric. Issue 9 (10th July 2020) - Britto, Gabriela Cristina Silva de; Bécker, Gisele; Soares, Willian Pinheiro; Nascimento, Edgar; Rodrigues, Erika Cristina; Picanço, Nágela Farias Magave; Faria, Rozilaine Aparecida Pelegrine Gomes de; Scabora, Márcia Helena
Abstract: This study aimed to evaluate the effect of the addition of different concentrations of turmeric powder to a dairy product with plantain syrup. The dairy product was supplemented with 50% plantain syrup (w:w) and six concentrations of turmeric powder. During 28 days of storage, the color parameters ( L *, a *, b *, H, and C *), water activity, oxidation, titratable acidity, pH, syneresis, water retention capacity (WRC), total soluble solids, carotenoids, antioxidant activity (DPPH), total phenolic compounds (TPC), centesimal composition, mineral contents (Ca, Na, and K), and microbiological quality were evaluated. Dairy products supplemented with turmeric were found to be more yellow ( b *) and showed a saturated color ( C *), lower syneresis rate, lower oxidation value, and greater antioxidant activity using DPPH, TPC, and WRC (at 28th day). The addition of turmeric to a dairy product improves the physicochemical properties, including increased calcium content, color enhancement, and improved antioxidant activity, during the product shelf life. Practical applications: In postharvest, some fruits rapidly reach the maturing stage which causes losses. The use of these vegetables in dairy products has shown significant results related to decreasing the waste in different stages of the production inside industries. Banana is a fruit that causes great losses in natura and it could be used in the formulation of dairy products. The addition of spices such as turmeric ( Curcuma longa L.) could improve the nutritional quality, enhancing the flavor, and color of the product developed by avoiding the addition of antioxidants and synthetic dyes. Dairy foods are excellent sources of vitamin B complex and minerals content. Together with the trends of the consumption of the population, the development of dairy products, which can provide nutritional value and health benefits, would encourage children to consume a foodstuff without synthetic additives.